Justice and Human Rights in the African Imagination We, Too, Are Humans - Eze, Chielozona (Routledge Contemporary Africa, 2021)
Justice and Human Rights in the African Imagination is an interdisciplinary reading of justice in literary texts and memoirs, films, and social anthropological texts in postcolonial Africa. 　 Inspired by Nelson Mandela and South Africa's robust achievements in human rights, this book argues that the notion of restorative justice is integral to the proper functioning of participatory democracy and belongs to the moral architecture of any decent society. Focusing on the efforts by African writers, scholars, artists, and activists to build flourishing communities, the author discusses various quests for justice such as environmental justice, social justice, intimate justice, and restorative justice. It discusses in particular ecological violence, human rights abuses such as witchcraft accusations, the plight of people affected by disability, homophobia, misogyny, and sex trafficking, and forgiveness. 　 This book will be of interest to scholars of African literature and films, literature and human rights, and literature and the environment.